PREDIABETES, PREHYPERTENSION AND RISK FOR ALL-CAUSE AND CARDIOVASCULAR MORTALITY AMONG US ADULTS: RESULTS FROM THE NATIONAL HEALTH AND NUTRITION EXAMINATION SURVEYS. (April 2021) - Chen, Chao-Lei; Liu, Lin; Huang, Jia -Yi; Yu, Yu-Ling; Shen, Geng; Lo, Kenneth; Huang, Yu -Qing; Feng, Ying -Qing
Abstract : Objective: Recent studies have suggested that prehypertension and prediabetes are associated with an increased risk for all-cause or cardiovascular mortality but the findings are inconsistent. The purpose of this study was to explore the associations of prehypertension alone, prediabetes alone, and prehypertension combined with prediabetes with risk for all-cause mortality and cardiovascular mortality among healthy US adults. Figure. No caption available. Design and method: Data for this study were obtained from the 1999–2014 National Health and Nutrition Examination Surveys (NHANES), a representative survey of the civilian, non-institutionalized US population conducted by the Center for Disease Control and Prevention (CDC). A total of 23622 participants without baseline hypertension, diabetes and cardiovascular disease (CVD) were enrolled after applying the inclusion and exclusion criteria. Prehypertension was defined as systolic/diastolic blood pressure: 120–139/80–89mmHg. Prediabetes was defined as fasting glucose 100–125 mg/dL or a hemoglobin A1c (HbA1c) between 5.7% and 6.4%. Participants were followed for cardiovascular and all-cause mortality through 31 December 2015. Cox proportional hazards models, sensitivity analyses and Kaplan-Meier survival curves were performed. Results: Overall, 12272 (51.95%) of subjects at baseline did not have prehypertension and prediabetes, 5841 (24.73%) had prehypertension alone, 2757 (11.67%) had prediabetes alone, and 2752 (11.65%) had both prehypertension and prediabetes. During a median follow-up of 8.58 years, a total of 1039 (4.40%) all-cause deaths and 98 (0.41%) CVD-related deaths occurred. Compared with participants without either prediabetes or prehypertension, the multivariable adjusted hazard ratios for all-cause mortality among participants with prehypertension alone, prediabetes alone, and both prediabetes and prehypertension were 1.01 (95% CI 0.79, 1.3), 1.13 (0.83, 1.53), and 1.17 (0.89, 1.55) (P for trend= 0.199), as well as for cardiovascular mortality were 1.40 (95%CI 0.59, 3.32), 1.31 (0.45, 3.83), and 1.61 (0.64, 4.05) (P for trend= 0.365), respectively. Subgroup analyses by age, gender, race, BMI, smoke status, TG and HDL-C showed no significant interaction. Conclusions: Our findings suggested that neither prehypertension nor prediabetes, as well as prehypertension with concomitant prediabetes, was associated with an increased risk for all-cause and cardiovascular mortality.